Mobile applications available in Saudi Arabia for the management of Primary Dysmenorrhea: A quality review and content analysis - Reem M. Alwhaibi; Halla H. Alrwaily; Fadiah A. AlJaloud; Sarah A. AlOfaisan; Norah F. AlSutami; Haneen M. AlEssa; Faisal M. Alessa; Ruqaiyah Khan; Tahani J. Alahmadi (PLoS ONE, 2025)
Background Primary dysmenorrhea (PD), common in women below 25 years, occurs as pain in the absence of any identifiable pelvic pathology. Menstrual tracking applications (MTAs) may help women manage their PD symptoms. No systematic assessment has been performed on MTA quality with respect to physical therapy management exercise. Objectives This study evaluated the quality of MTAs available in Saudi Arabia for mobile users in both the App Store and Google Play Store and assessed the quality and completeness of exercise regimens provided in these apps using the FITT principle as a guideline for managing PD symptoms. Methods In this cross-sectional study, apps were collected from the App Store and Google Play Store using two strategies for each store independently: Scraper and SimilarWeb. The app quality was evaluated using the Mobile Application Rating Scale (MARS), and exercise content was evaluated based on the recommended Frequency, Intensity, Time, and Type (FITT) principles. Results Final evaluation included 16 apps, of which 87.5% required subscription. The mean app quality score ranged from 2.54 (worst-rated app) to 4.45 (best-rated app) with a mean score of 3.54 ± 0.58. In addition, only three apps provided all the FITT components in the exercise content. Conclusion This study assessed the quality of exercise provided within these applications as interventions for managing PD symptoms. This evaluation contributes to the understanding of mobile health technologies for PD management in the region, and highlights areas for improvement in app development and content quality to better serve individuals with PD.